Antifungal activity of tree Chilean Plant Extracts on Botrytis cinerea - Vio Michaelis, S.=700 1 Apablaza Hidalgo, G.; Gomez, M.; Peña Vera, R.; Montenegro, G.
(Es, En)
Ilus., 20 ref.
Keywords: FUNGICIDAS; COMPUESTOS FENOLICOS; EXTRACTOS; ORGANISMOS INDIGENOS; EPHEDRA; CONTROL DE ENFERMEDADES; ENFERMEDADES FUNGOSAS; BOTRYTIS CINEREA; MEXICO; EPHEDRA BREANA; FABIANA IMBRICATA; NOLANA SEDIFOLIA